'Multivariate statistical analysis of relationship between tectonic activity and drainage behavior in Qorveh-Dehgolan basin Kurdistan, Iran'. Issue 5 (16th March 2021) - Sajadi, Payam; Singh, Amit; Mukherjee, Saumitra; Luo, Pingping; Chapi, Kamran; Salari, Mamand
Abstract: In this study, morphotectonic analysis was performed to investigate the influence of tectonic activity on drainage network in Qorve-Dehgolan basin, located in Sanandaj - Sirjan Zone (SSZ). Eight watersheds were delineated using burnt DEM and eleven morphotectonic indices including stream length gradient index (SL); drainage basin asymmetry (Af); hypsometric curve (HC); hypsometric integral (HI); roughness (R); elongation ratio (Re); mountain front sinuosity (Smf); basin shape (Bs); curvature of surface (C), basin slope (Sb) and river sinuosity index (K) were calculated. The higher altitude watersheds specifically showed various anomalies in the calculated indices. These indices when subjected to factor analysis (using Varimax rotation) resulted in extraction of "steepness factor" and "asymmetric factor" as two principal factors influencing the drainage network. The integrated analysis revealed that steepness factor, indicating ongoing tectonism, plays a significant role in the hydrology of higher altitude watersheds, whereas asymmetric factor is more dominant in lower altitude watersheds.